What we can Learn from Covid19 Pandemic: A Zoom Lens from Islamic Viewpoint Based on Hadith - Sahadevan, Mughaneswari; Azhar, Siti Mardhiyah Binti Kamal; Azizan, Nur Izzati Liyana Binti; Rahman, Nor Azura A (JURNAL ISLAM NUSANTARA, 2023)
This article explores the impact of the Covid-19 pandemic from an Islamic perspective, focusing on resilience, coping mechanisms, and community support through Hadith literature. Selected participants (Muslim) were recruited through random sampling from international students at the University Utara Malaysia. Interviewed them and asked four questions about their responses and reactions to issues during COVID-19. Analyzed the responses and their relation with compiling relevant Hadiths through an inductive reasoning approach. Utilizing qualitative interviews and analysis of Hadith teachings, the research delves into the responses and perceptions of Muslim individuals amidst the challenges posed by the pandemic. Findings reveal a deep-rooted faith and commitment to collective well-being among participants, manifested through proactive measures to protect families and patient acceptance of government regulations. The study highlights the resonance between respondents' actions and the timeless teachings of Islam, particularly in emphasizing the importance of caring for others, avoiding selfishness, and maintaining confidentiality regarding individuals' Covid-19 status. By integrating Islamic principles into the discourse on pandemic response, the research offers valuable insights for fostering resilience, solidarity, and compassion within Muslim communities and beyond. Ultimately, this study underscores the enduring relevance of Islamic teachings in navigating contemporary challenges and promoting a sense of unity and hope amidst adversity.